Identification Of Press Brick Composition As A Sound Absorbers - Wedayani, Ni Made; Antha Kasmawan, I Gde; Windaryoto, Windaryoto (BULETIN FISIKA; Vol 19 No 1 (2018): BULETIN FISIKA, 2018)
Abstract –  Sound absorption research using the press brick made of cement and sand has been done. The research was conducted to determine the effect of mixture on the absorption coefficient value of sound of the brick. In this research have made three variations ratio of cement : sand, that is 1:15, 1:10 and 1: 5 at pressure of 0.30 MPa. The physical quantity measured is the intensity of sound (dB) in the cube-shaped building model (74 x 74 x 68) cm 3 by using a sound level meter. The intensity of sound is determined by nomogram method by varying the sound frequency of 1 - 10 kHz for 5 minutes. It is found that the absorption coefficient value increases with increasing frequency. At frequency range of 1 – 6 kHz, brick with ratio cement : sand  of 1:15 has the highest absorption coefficient value, while at frequency range of 6 - 10 kHz,  brick with ratio cement : sand of 1: 5 which has the highest absorption coefficient value.